Eco-label Adoption in an Interdependent World - José-Antonio Monteiro (University of Neuchâtel, Institute of Economic Research (IRENE), 2010)
The growing popularity of national efforts to promote eco-labeling raises important questions. In particular, developing countries fear that the eco-label can deliberately impose the environmental concern of (high income) importing countries on their production methods. Yet, empirical studies of the adoption of eco-labelling schemes at the cross-country level are scarce due to the lack of data availability. In this paper, the decision to introduce an eco-label is analyzed through a heteroskedastic Bayesian spatial probit, which allows the government's decision to introduce an eco-label to be influenced by the behaviour of the neighbouring countries. The estimation is performed by extending the joint updating approach proposed by Holmes & Held (2006) to a spatial framework. Empirical evidence highlights the importance of a high stage of development, innovation experience and potential scale effects in the implementation of an eco-label scheme. In addition, results confirm the existence of a strategic interdependence in the eco-label decision.
Keywords: F18; C11; C25; 330; Bayesian Spatial Probit; International Trade; Environmental Policy; Eco-labelling